2004
DOI: 10.1590/s1415-47572004000300010
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetics of three Brazilian species of Eleutherodactylus (Anura, Leptodactylidae) with 22 chromosomes and re-analysis of multiple translocations in E. binotatus

Abstract: In this paper, we provide a cytogenetic analysis of Eleutherodactylus guentheri, E. parvus and E. binotatus. All of the species had a diploid chromosomal number of 2n = 22. The karyotypes of E. guentheri and E. parvus were very similar and differed only slightly in the morphology of pair 2. These two species also had an NOR-bearing secondary constriction on the long arms of pair 6. The karyotype of E. binotatus differed from those of E. guentheri and E. parvus in the morphology and size of the chromosomes, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 31 publications
0
17
2
Order By: Relevance
“…In S. aequifasciatus and S. haraldi, the formation of the chromosomal chains is probably a result of multiple translocations of small terminal segments of chromosomal pairs ( Figure 5). Similar mechanisms have been proposed to explain the multivalent configuration in the meiotic cells of the anuran amphibians Physalaemus petersi and Eleutherodactylus binotatus (Lourenço et al, 2000;Siqueira Jr et al, 2004). In general, the hybridization and the presence of heterozygous translocations reduce population fitness due to the formation of unbalanced gametes.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…In S. aequifasciatus and S. haraldi, the formation of the chromosomal chains is probably a result of multiple translocations of small terminal segments of chromosomal pairs ( Figure 5). Similar mechanisms have been proposed to explain the multivalent configuration in the meiotic cells of the anuran amphibians Physalaemus petersi and Eleutherodactylus binotatus (Lourenço et al, 2000;Siqueira Jr et al, 2004). In general, the hybridization and the presence of heterozygous translocations reduce population fitness due to the formation of unbalanced gametes.…”
Section: Discussionmentioning
confidence: 60%
“…The analysis of meiotic chromosomal configuration has been very useful for confirming the occurrence of polyploidization, duplication events and chromosomal rearrangements that took place during the chromosomal evolution of the mammals and other vertebrate groups (Villena and Sapienza, 2001;Dumas and Britton-Davidian, 2002;Siqueira Jr et al, 2004;Gallardo et al, 2006). If polyploidization or chromosomal rearrangements have occurred, then the meiotic chromosomal pairing becomes complex and can result in the production of unbalanced or balanced gametes (Sharp and Rowell, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Our sparse taxonomic sampling from this region makes it difficult to determine the composition of this group, but the joining of four diverse species (E. guentheri, E. hoehnei, E. parvus, and E. juipoca) in a well supported group, suggests that other species from the region believed to be closely related to them also are part of that group, which takes the available name Ischnocnema Reinhardt and Lütken, 1862 (see SI Text). Four southeast Brazilian species in our analysis that are not part of that clade are E. binotatus, which has an unusual karyotype (18), Holoaden bradei, Barycholos ternetzi, and Brachycephalus ephippium. These species also branch basally among eleutherodactylines but are not closely related to other species or groups.…”
Section: Resultsmentioning
confidence: 99%
“…Although the Giemsa-stained karyotypes strongly suggested that this heteromorphism resulted from reciprocal translocation, in our study it was definitely confirmed by comparative replication banding analysis. The structural rearrangement is most likely a sporadic finding that can occur in natural populations (Siqueira et al 2004, Schmid et al 2010. The results obtained so far us-ing silver impregnation revealed that this technique is widely useful for characterizing the species of Ololygon and Scinax (the former S. catharinae and S. ruber clades, respectively).…”
Section: Discussionmentioning
confidence: 99%